The past and future of minimum income benefits in Euskadi - Uribarri, Iñaki (Cuadernos de Trabajo Social, 2012)
This article summarizes the evolution of the regulations and policies of minimum income benefits in the war on poverty in Euskadi. The influence of the model used in some European countries is reflected in some of these actions which will soon become structural changes and will be integrated into the basic Public Administration budgets. In addition, the lines of action of the various platforms in the war on poverty and social exclusion in the region are analyzed in relation to the Autonomous Government’s minimum income benefits and the importance given to institutional policy by them, even though the modeling and management of them is critiqued.